Two-state model of conformational fluctuation in a DNA hairpin-loop - Ying, L; Wallace, M; Klenerman, D (2001)
Stretched exponential kinetics have been observed in the conformational fluctuation of a DNA hairpin-loop under equilibrium conditions. In this paper, we employ a simple multiple-pathway two-state jump model to calculate single-molecule proximity ratio distributions. The simulation can reasonably reproduce the experimental single-molecule data of the conformational fluctuations in water, indicating that static disorder is dominant. In contrast, there exists significant discrepancy between the two-state simulation and experiment in buffer (2.5 mM Tris-HCl, 250μM EDTA, 100 mM NaCl), suggesting that both static and dynamic disorder may contribute to the non-exponential kinetics. © 2001 Elsevier Science B.V.